Transforming Market-Driven Strategies in the Indonesian Medical Device Industry: Impact Analysis of Regulatory Compliance, Innovation, and Service Quality on Brand Loyalty - Yudakusuma, Marcell Wijaya (Golden Ratio of Marketing and Applied Psychology of Business, 2026)
This study examines how regulatory compliance, product innovation, and service quality contribute to market-driven strategy transformation in the medical device industry and influence customers’ brand loyalty, specifically in the Indonesian medical device industry. Data were collected using self-administered surveys from 120 institutional customers of a medical device manufacturing company in Indonesia as part of a quantitative research design and analyzed using structural equation modeling (SEM). The findings demonstrated that product innovation, service quality, and regulatory compliance all had significant effects on brand image (p < 0.05), with service quality being the most significant predictor (β = 0.503).  Brand loyalty was positively and significantly impacted by brand image (β = 0.587; p < 0.001).  Product innovation was found to have a significant direct impact on loyalty (β = 0.389; p < 0.001), whereas regulatory compliance had an indirect impact through brand image (p < 0.05) but no direct impact on loyalty (p > 0.05). These Findings imply that medical device sector in Indonesia should prioritize market-driven strategies which integrate service quality excellence and continuous product innovation, while also positioning regulatory compliance as credibility foundation to empower brand image and sustain customer loyalty.